ISO 9001:2008 System. Implementation experience in a small and medium enterprise of industrial clothing in the Peru, with emfhasis on production - Valencia Borda, Raúl (2013)
To apply a Quality Management System (QMS) in small business, is a worth experience and also it is an example for others in Peru. This is the reason why we describe this experience that is due to a work done to implement the QMS ISO 9001:2008 with an emphasis on production, in a small company of industrial garment, being this, the first in the country to certify in that field. The article points out the requirements and the proper procedure to be followed by a small industrial clothing company to achieve a successful implementation in their organizations and obtain the certification.